2017
DOI: 10.1007/s11365-017-0443-x
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling antecedents and performance effects of family SME innovation: A knowledge-based perspective

Abstract: Understanding how family small and medium-sized enterprises (SMEs) seize opportunities for innovation and thus achieve superior performance is of substantial interest to family firm managers and academia. This paper develops a conceptual framework of antecedents that include resources internal and external to the firm in the two major dimensions of technological innovation (TI) and management innovation (MI) and their effects on financial performance. The framework is empirically tested with survey data from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 103 publications
(162 reference statements)
3
18
0
Order By: Relevance
“…In March 2020, a link to the online survey was sent to 351 randomly selected SMEs by google form, resulting in 193 fully and correctly completed questionnaires. The overall response rate of 4.65% was similar to related studies in SME research [58].…”
Section: Methodssupporting
confidence: 84%
“…In March 2020, a link to the online survey was sent to 351 randomly selected SMEs by google form, resulting in 193 fully and correctly completed questionnaires. The overall response rate of 4.65% was similar to related studies in SME research [58].…”
Section: Methodssupporting
confidence: 84%
“…[28,51]. In this respect, prior studies have revealed a clearer direct positive effect of innovation outputs on performance indicators than that displayed in the case of innovation inputs [32,52,53].…”
Section: Innovation Inputsmentioning
confidence: 84%
“…Despite this general result, research exploring KM in the FF context (Zahra et al 2007;Chirico and Salvato 2008;Patel and Fiet 2011;Cunningham et al 2016;Letonja and Duh 2016) is still scarce and partial, and practically none of the existing studies exploring KM in FF analyzed its effects on firm innovation (Serrano-Bedia et al 2018a), leaving an evident a gap in this field. The only exceptions identified are the studies of Serrano-Bedia et al (2016); Kallmuenzer andScholl-Grissemann (2017), andSerrano-Bedia et al (2018a). Serrano-Bedia et al (2016) reported a negative moderating effect of CEO tenure, CEO-founder duality, and family involvement on the positive relationship between the use of various types of knowledge sources and innovation performance.…”
Section: Kmp and Innovation Outcomesmentioning
confidence: 99%
“…Serrano-Bedia et al (2016) reported a negative moderating effect of CEO tenure, CEO-founder duality, and family involvement on the positive relationship between the use of various types of knowledge sources and innovation performance. Kallmuenzer and Scholl-Grissemann (2017), for their part, investigated the effect of knowledge internalization and external knowledge on the technological and management innovation of family businesses. Finally, Serrano-Bedia et al (2018a) found that being a family firm negatively moderated the positive link between creation and the storage of new knowledge and innovation, and positively moderated the negative (but non-significant) link between knowledge transfer and innovation.…”
Section: Kmp and Innovation Outcomesmentioning
confidence: 99%